The Current State of the Level of Digitalization of the Public Administration System of the Republic of Armenia - Melkumyan, Narek («Տնտեսագետ» հրատ․)
Localizing digital technologies in the country's public administration system is one of the key prerequisites for enhancing its efficiency and ensuring transparency and accountability. The article's main purpose is to assess the current state of digitalization of the economy and the public administration system of the Republic of Armenia by studying the main indicators of national statistical bodies and international reports. International indexes, like the Network Readiness Index and the E-Government Development Index, have classified the degree of digitalization of Armenia's state system as average, highlighting the importance of several initiatives and measures implemented. Within the framework of the article, a three-level pyramid was also proposed to evaluate the digitalization situation of the state system of Armenia. According to that analysis, measures aimed at e-governance in the state system of Armenia are at a fairly good level, initiatives in digitization have just begun to appear, and clear, concrete steps and mechanisms are needed in the direction of digital transformation. The main results of the analysis show that the availability of investments, a stable digital environment, and the prerequisites for continuous education are of great importance for the digitalization of public administration in Armenia.
Keywords: Management